Somatosensory stimulation to improve hand and upper limb function after stroke—a systematic review with meta-analyses. Issue 2 (17th February 2018) - Grant, Virginia Marie; Gibson, Alison; Shields, Nora
Abstract: Background: Somatosensory stimulation may have a positive impact on recovery of motor function by maintaining cortical representation of the hand and acting to prime the motor system for movement. Objective: Determine the efficacy of somatosensory stimulation on upper limb motor function after stroke. Methods: Five electronic databases (MEDLINE, CINAHL, Embase, PEDro and OT Seeker) were searched from inception to October 2016. Included studies were English-language randomized controlled trials where a sensory intervention was applied below the elbow to improve upper limb motor control of adults after stroke. One outcome needed to measure arm function at an impairment or activity level. Study selection and quality assessment (using the PEDro scale) were independently conducted by two reviewers. Meta-analysis was completed where there was sufficient homogeneity between trials. Results: Fifteen articles were included reporting data from 14 randomized controlled trials (627 participants). There was low-quality evidence from four trials that sensory electrical stimulation did not improve upper limb activity compared to placebo (SMD 0.4, 95%CI −0.07 to 0.87, I 2 38%) and moderate-quality evidence from three trials that it did not improve motor impairment (MD 3.45 units, 95%CI −1.47 to 8.36, I 2 35%). Low-quality evidence from two trials demonstrated that therapist-delivered sensory stimulation did not improve upper limb activity (SMD 0.25, 95%CI −0.20 to 0.69, I 2 0%) compared to usual care. Conclusion: Current low- to moderate-quality evidence suggests somatosensory stimulation is not effective in improving upper limb motor impairment or activity after stroke.